Control de la pudrición de la corona en los clusters de banano con cuatro fungicidas - Arévalo Ramón, Stalin Alonso (2010)
In the country property San Luis of the cantón Machala, one carries out the present experimental work, relative to the application of systemic fungicides and of action translaminar, to control the pudrición of the crown that one of the causes of economic losses constitutes, for the producers and exporters. The outlined objectives were: 1. - to establish the difference in percentage of control of the pudrición of the crown with Vivando in front of Mertec, Regnum and Bankit; 2. - to determine the best vivando dose to control the pudrición of the crown of those clusters. The fungicides employees were: Bankit 0.5 g; Vivando 0.75 g; Regnum 1.0 g. and Mertec 500 ml. The products were applied to the clusters after the heavy of the fruit, using a brush. The pudrición of the crown you determines to those to 10, 14 and 18 days, taking out one by one for line the clusters and with a previously established scale you will it proceeded to evaluate the damage as much in the crown as in the neck of the fingers. The grade of maturation of each treatment you evaluated with the help of the scale of Von Cesacke. For investigation a box of banana tree of 43 pounds was chosen, of the variety cavendish for each treatment in the packer of the Treasury “San Luis”, giving in total 20 boxes per week. The obtained results were analyzed at random by means of a mathematical model of the Design in completely with sub sampling. The pudrición of the crown caused by pathogen mushrooms of I generate them Gleosporum musarum, Boroglycerinate, in packed fruit, showed and starting from the 14 days in the boxes with fruit tried with the four fungicides raising infestation levels of until 68,5% of the cluster of a box. The best product for the smallest level in pudrición of the crown was the Pyraclostrobin (Regnum). The maturation grade reached by the fruit in the interval of time that I last the investigation was similar in all the treatments.